Development Of Teaching Materials With Dayak Kanayatn Traditional Tool Context On Mathematical Connection Ability In Class V Students Of SD Negeri 06 Ngabang - Jesica Esha Risty; Muhamad Firdaus; Hartono Hartono (Universitas Negeri Makassar, 2020)
This study aims to develop and assess the quality of mathematics teaching materials with the context of traditional Dayak Kanayatn tools on the ability of students' mathematical connections on valid, practical, and effective two dimentional figure. The type of research used is Research & Development (R&D) research with reference to the 4-D model, namely Define, Design, Development, and Disseminate. The test subjects in this study were grade V students of SD Negeri 06 Ngabang with a total of 22 students. Based on the results of limited trials conducted, it was found that 1) the results of the validation of teaching materials were 76.97% in the valid category, 2) the results of practicality based on observations of the implementation of teaching materials developed showed that teaching materials with very practical categories, 3) the results of the effectiveness of the materials teaching is 73.33% with the effective category. So it can be concluded that at the limited trial stage a mathematics teaching material is carried out in the context of the traditional Dayak Kanayatn tool that has met the criteria of validity, effectiveness, and effectiveness of the ability of mathematical connections